Use of Electronic Information Resources in the Pedagogical Process - Umarova, Nodirakhon Isamatovna (PT. Antis International Publisher, 2024)
This article is about the technologies of electronic textbooks, and opinions are given about the importance of students' use of electronic information resources and the integration of education with modern production.